Perang Dagang Amerika Serikat dan Tiongkok: Bagaimana Dampaknya Bagi Perekonomian Indonesia Tahun 2017 - 2020? - Sitorus, Destri Sambara (Universitas Pendidikan Ganesha, 2021)
The trade war that began with the foreign policy of the President of the United States, Donald Trump, who imposed tariffs on goods from China, triggered China to retaliate against this policy with various other forms of protection. This has an impact on global economic growth, especially for countries that have a lot of cooperation with the two countries, including Indonesia. As for countries like Indonesia, which depend a lot on economic cooperation with the two countries, especially in the export and import sectors, it is certainly affected by their economic growth. This research is a descriptive qualitative study that aims to explain how the impact of the trade war between the United States and China on the Indonesian economy in 2017 - 2020 using foreign policy theory and the concept of protectionism. The results of the study show that the trade war between the United States and China has had a significant impact on the Indonesian economy, especially in the export sector and stock investment.